Aplikasi Pengenalan Bahasa Mongondow Dengan Speech Recognition Menggunakan Metode Rapid Application Development (RAD) - Priyo Perdana Adati; Parabelem T. D. Rompas; Olivia Kembuan (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
Indonesia is a nation with a diversity of languages and cultures. The regions in Indonesia have several different languages as a medium for communication. Language itself has an important value in the daily life of today's society because it is a means of communication. Besides that, language also includes self-identity and culture. Therefore preserving regional languages is important. This research aims to design a mobile-based Mongondow language recognition application that is easy for Android users to use anywhere and anytime. The developer method used for designing this application is Rapid Application Development (RAD). Designing and developing this application uses the Kodular website with drag-and-drop block programming features without having to type coding. From the research that has been done, an application for the introduction of the Mongondow language will help the general public and young people, especially those in Bolaang Mongondow, in learning the local language. Also, the community can prevent the loss of their mother tongue in their area.